Injury severity of pedestrians, bicyclists and motorcyclists resulting from crashes with reversing cars. (September 2016) - Decker, Sebastian; Otte, Dietmar; Cruz, Dana Leslie; Müller, Christian Walter; Omar, Mohamed; Krettek, Christian; Brand, Stephan
Highlights: First analysis of vulnerable road users after collisions with reversing vehicles. Lower extremities are of highest risk for severe injuries and are injured most often. An abbreviated injury scale classification of 4–6 is uncommon. Abstract: Objective: Pedestrians, bicyclists and motorcyclists can suffer serious injury in road traffic crashes. To date, no studies examine the injury severity within this vulnerable cohort following collisions with reversing cars. Material and methods: Our institution prospectively maintains a database including medical and technical information regarding traffic accidents in our area, including urban and suburban regions. In a retrospective review of this database, the authors describe the injury severity of pedestrians, bicyclists and motorcyclists following traffic crashes involving reversing cars. Injury severity was described using the abbreviated injury scale (AIS) as well as the maximum abbreviated injury scale (MAIS). Results: This study included 234 crashes occurring between 1999 and 2012. The lower extremity was injured most often while also suffering more severe injuries with a median AIS of 1 compared to 0 in all other documented body regions. The upper extremity was injured second most often. AIS ranging from 4 to 6 were infrequent. AIS 3 however, was documented for the legs in 4.3% of patients. MAIS 0, 1, 2, 3, 5 and 9 were found in 1, 164, 46, 14, 1, and 8 patients in the study cohort, respectively. Pedestrians and motorcyclists were seriously injured in 9.1% and 9.6% of cases, respectively. In contrast, no bicyclists suffered serious injuries. As to the zone of impact, most collisions occurred at the rear center of the vehicle (35%) followed by rear left (26%), rear right (20%), side rear (11%), side center (4%) and side front (3%). 204 (87.2%) collisions occurred during the day, 19 (8.1%) at night and 11 (4.7%) at twilight. Speed was similar in crashes involving pedestrians, bicyclists and motorcyclists, being as high as 7.0 ± 3.6, 7.0 ± 4.0 and 7.9 ± 4.2 km/h respectively. Conclusions: This is the first study that analyzes injury severity among these vulnerable road users following collisions with reversing vehicles. The majority of collisions occur at low impact speed during the day. Most injuries resulting from these collisions are not serious, however pedestrians are at greatest risk of severe injury to any body region. The lower extremities suffer the most serious and frequent injuries within this cohort.